SISTEM PEMBAGIAN WARISAN PADA MASYARAKAT MUSLIM DI KOTA MAKASSAR - Andi Herawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Rules regarding the transfer of property of a deceased person (heir) to his surviving heirs are sub-systems of Islamic law. Islam as a universal teaching teaches all aspects of human life, including in terms of the distribution of inheritance fairly. The practice of inheritance sharing in Muslim communities in the city of Makassar is very varied, there are by way of grants, deliberations or compromises, approaches to Islamic inheritance law, and also through mediation initiated by religious courts. Such resolution efforts are called resolutions through non-litigation channels, while efforts to distribute inheritance through court decisions are called settlement through litigation.